1997
DOI: 10.1021/tx960149h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Depurinating DNA Adducts Formed by One-Electron Oxidation of 7H-Dibenzo[c,g]carbazole and Identification of These Adducts after Activation with Rat Liver Microsomes

Abstract: It is hypothesized that 7H-dibenzo[c,g]carbazole (DBC) is metabolically activated by one-electron oxidation in accordance with its propensity to be easily oxidized to its radical cation. Iodine oxidation of DBC produces a radical cation that subsequently binds to nucleophilic groups of dG or Ade. Oxidation of DBC in the presence of dG products three adducts: DBC-5-N7Gua, DBC-6-N7Gua, and DBC-6-C8Gua, whereas in the presence of Ade, four adducts are obtained: DBC-5-N7Ade, DBC-5-N3Ade, DBC-5-N1Ade, and DBC-6-N3A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…A significant level of Fpg-sensitive sites detected in DiMeDBC-treated cells suggest that either oxidative DNA damage or unstable DNA adducts formed by one-electron oxidation [Chen et al, 1997] might underlie the biological activity of DiMeDBC in human hepatoma cells. Our results are in line with previous ones determined in the rat progenitor WB-F344 cells [Valovicova et al, 2009] and in the Chinese hamster V79MZh1A2 cells [Gabelova et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…A significant level of Fpg-sensitive sites detected in DiMeDBC-treated cells suggest that either oxidative DNA damage or unstable DNA adducts formed by one-electron oxidation [Chen et al, 1997] might underlie the biological activity of DiMeDBC in human hepatoma cells. Our results are in line with previous ones determined in the rat progenitor WB-F344 cells [Valovicova et al, 2009] and in the Chinese hamster V79MZh1A2 cells [Gabelova et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [1997] have demonstrated that DBC forms unstable depurinating DNA adducts through radical cations generated by one-electron oxidation. With DBC, this biotransformation pathway is supposed to be only a minor one [Dowty et al, 2000].…”
Section: Discussionmentioning
confidence: 99%
“…Although DBC, which has a relatively low ionization potential [Xue et al, 1999], can form depurinated DNA adducts through radical cations by one-electron oxidation [Chen et al, 1997], this mechanism is a minor metabolic pathway in mouse liver and lung [Dowty et al, 2000]. Recently, Xue et al [2002] have presented a potential metabolic activation mechanism of DBC via an o-quinone that results in both stable and depurinating DNA adduct formation.…”
Section: Introductionmentioning
confidence: 99%
“…The human cytochrome P450 1A (CYP1) and 3A (CYP3A) families of enzymes have been shown to be involved in DBC biotransformation [Mesarosova et al, ; Valovicova et al, ; Gabelova et al, ] and the monohydroxylated derivatives are the major DBC metabolites [Warshawsky et al, ]. Because of a relatively low ionization potential, the radical‐cation can also be involved in DBC metabolism via one‐electron oxidation, though it may represent only a minor metabolic pathway [Chen et al, ; Dowty et al, ]. In addition, DBC undergoes aldo‐keto reductase‐catalyzed oxidation, and DBC‐3,4‐dione is supposed to be the ultimate metabolite of this carcinogen [Xue et al, ].…”
Section: Introductionmentioning
confidence: 99%